Simetria quiral: fótons, píons e núcleons - Pupin, Joel César [UNESP] (Universidade Estadual Paulista (Unesp), 1994)
In this Work we study the role played by chiral and electromagnetic gauge symmetries, the weak constant 'g IND. A' and pion-nucleon couplings in three processes; single and double pion photo production and photon-nucleon interaction. The first two of them are treated at tree levei, whereas the last one includes one loop corrections. The role of the symmetries is analyzed considering the existence of relationships among various diagrams contributing to a given process. The influence of the way pions couple to nucleons is studied by comparing results obtained by means of the linear sigma model and the non linear model proposed by Weinberg. Finally, the role of 'g IND. A' is assessed by direct inspection of formal expressions. Our study showed that chiral symmetry is relevant only for double pion photo production. In particular, chiral symmetry does not influence the pion cloud contribution to the electromagnetic nucleon form factor, at least within the one loop approximation considered. These results pave the way for more comprehensive studies of the role of chiral symmetry in non perturbative approaches, such as the Skyrme model

Este trabalho consiste no estudo do papel das simetrias quiral e de calibre eletromagnético, da constante 'g IND. A' e do tipo de acoplamento pion-núcleon em três processos: fotoprodução de um píon e de dois píons e interação fóton-núcleon. Os dois primeiros processos são tratados na aproximação em árvore, enquanto que no último são considerados também diagramas envolvendo um loop. O papel das simetrias é analisado investigando-se a existência de relações entre os vários diagramas de um dado processo. Já o papel do tipo de acoplamento pion-núcleon é analisado, comparando-se os resultados obtidos por meio de dois modelos de implementação da simetria quiral: o sigma linear e o não linear de Weinberg. Analogamente, o papel de 'g IND. A' é avaliado pela inspeção direta das expressões obtidas para os vários processos. Este estudo mostrou que, apenas no processo envolvendo dois píons externos a simetria quiral é relevante. Em particular, a simetria quiral é irrelevante para o fator de forma eletromagnético devido à nuvem piônica do núcleon, pelo menos no contexto das correções de um loop consideradas. Estes resultados constituem pontos de partida para o estudo mais abrangente do papel da simetria quiral em abordagens não perturbativas, tais como a do modelo de Skyrme
Keywords: Partículas (Física nuclear) - Quiralidade; Fótons; Pions; Particles (Nuclear physics) - Chirality